Incidence and Predictors of Cardiac Arrhythmias in Patients With COVID-19 - Mouram, Sahar; Pannone, Luigi; Gauthey, Anaïs; Sorgente, Antonio; Vergara, Pasquale; Bisignani, Antonio; Monaco, Cinzia; Mojica, Joerelle; Al Housari, Maysam; Miraglia, Vincenzo; Del Monte, Alvise; Paparella, Gaetano; et al. (Frontiers in Cardiovascular Medicine, 2022)
Background: Coronavirus disease-19 (COVID-19) is a systemic disease caused by severe acute respiratory syndrome coronavirus 2. Arrhythmias are frequently associated with COVID-19 and could be the result of inflammation or hypoxia. The aim of this study is to define the incidence of arrhythmias in patients with COVID-19 and to correlate arrhythmias with pulmonary damage assessed by computed tomography (CT). Methods: All consecutive patients with COVID-19 diagnosis, hospitalized at Universitair Ziekenhuis Brussel, Belgium, between March 2020 and May 2020, were screened. All included patients underwent a thorax CT scan and CT severity score, a semiquantitative scoring system of pulmonary damage, was calculated. The primary endpoint was arrhythmia occurrence during follow-up. Results: One-hundred patients were prospectively included. At a mean follow-up of 19.6 months, 25 COVID-19 patients (25%) experienced 26 arrhythmic episodes, including: atrial fibrillation in 17 patients, inappropriate sinus tachycardia in 7, atrial flutter in 1 and third-degree atrioventricular block in 1. No ventricular arrhythmias were documented. COVID-19 patients with arrhythmias showed more often need for oxygen, higher oxygen maximum flow, longer QTc at admission and worse damage at CT severity score. At univariate logistic regression analysis significant predictors of primary endpoint were: need for oxygen therapy (OR 4.59, 95% CI 1.44-14.67, p=0.01) and CT severity score of pulmonary damage (OR per 1 point increase 1.25, 95% CI 1.11-1.4, p<0.001) Conclusions: In a consecutive cohort of COVID-19 patients the incidence of cardiac arrhythmias was 25%. The need of oxygen therapy and CT severity score were predictors of arrhythmia occurrence during follow-up.